The syntax of relative clauses : a unified analysis - Cinque, Guglielmo (New York: Cambridge University Press, 2020)
Relative clauses play a hugely important role in analysing the structure of sentences. This book provides the first evidence that a unified analysis of the different types of relative clauses is possible - a step forward in our understanding. Using careful analyses of a wide range of languages, Cinque argues that the relative clause types can all be derived from a single, double-headed, structure. He also presents evidence that restrictive, maximalizing, ('integrated') non-restrictive, kind-defining, infinitival and participial RCs merge at different heights of the nominal extended projection. This book provides an elegant generalization about the structure of all relatives. Theoretically profound and empirically rich, it promises to radically alter the way we think about this subject for years to come.
Keywords: English language -- Relative clauses; Electronic books